Association of lewy bodies, hippocampal sclerosis and amyloid angiopathy with dementia in community-dwelling elderly: A systematic review and meta-analysis. (August 2021) - Avan, Abolfazl; Amiri, Amin; Mokhber, Naghmeh; Erfanian, Mahdiyeh; Cipriano, Lauren E.; Stranges, Saverio; Shojaeianbabaei, Golnaz; Abootalebi, Shahram; Azarpazhooh, M. Reza
Highlights: We found 14 studies comprising 2197 demented and 2104 non-demented community people. Dementia risk increased with Lewy body, hippocampal sclerosis, and amyloid angiopathy. With neocortical Lewy bodies, 20% of participants remained non-demented until death. With bilateral hippocampal sclerosis, 17% of people remained non-demented until death. With moderate/severe amyloid angiopathy, 42% remained non-demented until death. Abstract: Introduction: We measured the proportion of Lewy body pathology (LB), hippocampal sclerosis (HS), and cerebral amyloid angiopathy (CAA) among community-dwelling people with and without dementia. Methods: We searched for community-based cohorts with postmortem brain autopsy until 1 January 2020. We calculated the summary risk difference and 95% confidence interval (95% CI) using a random-effects model in R. Results: We found 12 articles, comprising 2197 demented and 2104 non-demented participants. LB, HS, CAA were prevalent lesions among community-dwelling elderly (15%, 10%, and 24%, respectively). These significantly increased the risk of dementia (LB: risk difference 38%, 95% CI 20–56%, HS: 34%, 24–44%, CAA: 19%, 3–34%). 20% of cases with neocortical LB, 17% with bilateral HS, and 42% with moderate/severe CAA pathology remained non-demented by death. Discussion: LB or HS or CAA are common neuropathologies among community-dwelling elderly. Although these lesions independently are associated with dementia, many remain non-demented, by death.